Ketogenic Diet for KARS-Related Mitochondrial Dysfunction and Progressive Leukodystrophy - Murofushi, Yuka; Hayakawa, Itaru; Abe, Yuichi; Ohto, Tatsuyuki; Murayama, Kei; Suzuki, Hisato; Takenouchi, Toshiki; Kosaki, Kenjiro; Kubota, Masaya (Neuropediatrics, 2021)
KARS encodes lysyl-tRNA synthetase, which is essential for protein translation. KARS mutations sometimes cause impairment of cytoplasmic and mitochondrial protein synthesis, and sometimes lead to progressive leukodystrophies with mitochondrial signature and psychomotor regression, and follow a rapid regressive course to premature death. There has been no disease-modifying therapy beyond supportive treatment. We present a 5-year-old male patient with an asymmetrical leukodystrophy who showed overt evidence of mitochondrial dysfunction, including elevation of lactate on brain MR spectroscopy and low oxygen consumption rate in fibroblasts. We diagnosed this patient's condition as KARS-related leukodystrophy with cerebral calcification, congenital deafness, and evidence of mitochondrial dysfunction. We employed a ketogenic diet as well as multiple vitamin supplementation with the intention to alleviate mitochondrial dysfunction. The patient showed alleviation of his psychomotor regression and even partial restoration of his abilities within 4 months. This is an early report of a potential disease-modifying therapy for KARS-related progressive leukodystrophy without appreciable adverse effects.
Keywords: KARS; progressive leukodystrophy; psychomotor regression; mitochondrial dysfunction; ketogenic diet; vitamin supplementation